PENGARUH PENERAPAN PENDEKATAN SAINTIFIK (SCIENTIFIC APROACH) TERHADAP KEMAMPUAN KOMUNIKASI SISWA KELAS IV - Markiya, Markiya; Sari, Tita Tanjung; Puniman, Ach. (FKIP Universitas Wiraraja, 2019)
Problems faced by students in integrated thematic learning are 1) learning activities are still dominated by using the lecture method; 2) lack of students' ability to ask questions and express opinions; 3) lack of application of student-centered learning approaches. Of the several problems experienced by students in learning activities resulting in low student learning outcomes, especially on student communication skills. The purpose of this study was to determine how the application of the scientific approach to integrated thematic learning and to determine the effect of the application of the scientific approach to students' communication skills on integrated thematic learning in class IVB MIN 2 Sumenep. This research uses quasi experimental design. in the form of nonequivalent control group design. The sample in this study consisted of two classes, namely class IVA and class IVB. Class IVA as many as 24 students as the control class and class IVB as many as 24 students as the experimental class. The treatment applied to the experimental class is the scientific approach. the steps of learning activities with a scientific approach in this study are 1) Observing; 2) Asking questions; 3) Gathering Information; 4) Processing information and; 5) Communicating. The results of this study indicate that: 1) the application of using a scientific used in the experimental class is more effective than the control class; 2) the application of scientific learning has a significant effect on students' communication skills in integrated thematic learning in class IVB MIN 2 Sumenep. This is evidenced by the results of the t-test 2 Free Samples (Independent Sample Test). Where in the t-test 2 free samples (independent sample t-test) obtained the value of t count 3.347> t table 1.679, then Ho is rejected and Ha is accepted.